Enhancing the Cassava Value Chain: Policy Recommendations and Strategies for Sustainable Development - Wongpit, Piya; Boungvatthana, Thone; Xaysombath, Amphone; Chanhthalangma, Vilaphanh (Research on World Agricultural Economy, 2024)
Cassava has emerged as a significant cash crop in the Lao People’s Democratic Republic, driven by the establishment of starch factories and favorable government policies promoting foreign direct investment. This study analyzes the cassava value chain in Champasak Province, the second-largest producer in the country, to identify key challenges and opportunities for enhancing the sector’s sustainability and profitability. Through comprehensive mapping of stakeholders including farmers, traders, processing companies, exporters, and buyers, this research highlights critical issues such as land use, infrastructure development, market access, and financial support. Policy recommendations are provided to improve cassava production practices, enhance market linkages, and create conducive regulatory environments. The findings aim to guide policymakers and stakeholders in developing strategies that bolster the cassava value chain, contributing to economic growth and sustainable development in Lao PDR.